THE SPEED AND NATURE OF THE WITHERING OF LEAVES OF PLANTS GERANIUM-KOPEECHNIKOVY MEADOWS OF THE NORTH-WEST CAUCASUS - M. A. Erkenova (Юг России: экология, развитие, 2014)
Dynamics of dying leaves investigated the eighteen species of herbaceous plants geranium-kopeechnikovy meadows in the Teberdinsky reserve.The duration of the withering away of the individual leaves of summer-green plants geranium-kopeechnikovy meadows is on average from 9.6 to 11.8 days. Leaves of summer generation in the summer-winter-green plants die off from 10.2 days (Luzula multiflora) to 14.3 days (Carex atrata), while the leaves, leaving the winter green die within a few months. The Rhododendron caucasicum part of the leaves died out in the average for the 14.9 days, and the leaves, dying for several seasons - within 10 months.